Primary Non-Hodgkin’s lymphoma originating from the masseter muscle (Bangladesh Journal of Medical Science, 2021)
Recently, as we experienced a case of extranodal NHL originating from the masseter musclecompletely cured by chemotherapy with radiotherapy, we present the clinical, US, CT, andMR imaging findings in additional one case of biopsy-proved extranodal NHL (NK/T celllymphoma) involving predominantly the masseter muscle also review thoroughly our collectedcases of primary non-Hodgkin’s lymphoma involving the muscles of mastication and facialexpression. On the basis of our comprehensive review, we suggest two conclusions. First, primarymuscle lymphoma particularly originating from muscles of mastication and facial expression isextremely rare, but primary muscle lymphoma should be considered in the differential diagnosisof muscular masses. Second, primary muscle lymphoma particularly originating from muscles ofmastication and facial expression has similar clinical and radiological characteristics to primaryskeletal muscle lymphoma involving other sites. However, the prognosis is more favorablein primary muscle lymphoma originating from muscles of mastication and facial expressioncompared to primary skeletal muscle lymphoma involving other sites.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.181-186